2008
DOI: 10.1158/1055-9965.epi-07-2775
|View full text |Cite
|
Sign up to set email alerts
|

Line Region Hypomethylation Is Associated with Lifestyle and Differs by Human Papillomavirus Status in Head and Neck Squamous Cell Carcinomas

Abstract: Genomic hypomethylation is a hallmark of essentially all cancers, but the degree of this hypomethylation differs among individual tumors. Little work has explored what leads to these differences and or asked whether they are clinically meaningful. In this study of head and neck squamous cell carcinoma, we assessed hypomethylation in tumors using a semiquantitative fragment analysis approach to determine the relative methylation status of the line retroviral element LRE1 (Line-1.2). Because this is an establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…Seventeen articles met the inclusion criteria and were eligible for further analysis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The main reasons for exclusion were duplicates and studies not investigating correlation between HPV status and methylation status in OPSCC.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventeen articles met the inclusion criteria and were eligible for further analysis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The main reasons for exclusion were duplicates and studies not investigating correlation between HPV status and methylation status in OPSCC.…”
Section: Search Resultsmentioning
confidence: 99%
“…28,33,34,44 In other publications studying overall HNSCC, OPSCC subgroup size ranged from 9% to 80% of the total study population. [29][30][31][32][35][36][37][38][39][40][41][42][43] There was only one study that reported the distribution of average age, nicotine and alcohol consumption between HPV-positive and HPV-negative tumors of which promoter methylation was evaluated. 34 The mean age in HPV-positive tumors was 56.9 compared with 58.4 in HPV-negative tumors.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations